Effects of Military Alliances on Regional Security: A Study of NATO's Presence in Eastern Europe - Sinani, Hellen (American Journal of International Relations, 2024)
Purpose: The aim of the study was to assess the effects of military alliances on regional security, a study of NATO's presence in Eastern Europe. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: NATO's presence in various regions has significantly enhanced security and stability through its collective defense mechanism, which deters potential aggressors. The alliance's strategic deployments and military exercises bolster the defense capabilities of member states, providing a robust security framework. Additionally, NATO's involvement in crisis management and conflict prevention contributes to regional stability by addressing emerging threats and fostering cooperation among member nations. However, the study also highlights potential drawbacks, such as the escalation of tensions with non-member states, particularly Russia, which perceives NATO's expansion as a threat to its sphere of influence. Overall, while NATO's presence generally promotes regional security, it necessitates careful management of international relations to mitigate adverse geopolitical reactions. Implications to Theory, Practice and Policy: Realist theory, constructivist theory and institutionalism theory may be used to anchor future studies on assessing the effects of military alliances on regional security, a study of NATO's presence in Eastern Europe. In terms of practical applications, stakeholders should encourage and facilitate collaboration among NATO member states and partner countries in Eastern Europe. From a policy perspective, it is essential to advocate for transparent and inclusive dialogue between NATO and non-member states in Eastern Europe